Are double translocations double trouble? - Bowser-Riley, S M (1988)
Double translocation heterozygotes are rare, but need not necessarily pose more of a counselling problem than single reciprocal translocation heterozygotes. Nine cases of double translocation are presented, together with a review of the few reports published to date. An attempt is made to provide simple counselling guidelines in the assessment of the risk of producing a liveborn abnormal child. This is not based on theoretical considerations of segregation patterns, but extrapolated from what is known empirically about the viable segregation patterns in carriers of single reciprocal translocations. It assumes that there is no interference with the independent assortment of the two separate exchanges, unless a common participating chromosome is involved. The possibility of an interchromosomal effect has not been taken into consideration.